PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN KETERAMPILAN MENULIS KREATIF CERITA PENDEK SISWA KELAS XI SMA NEGERI 1 LUWU - Rahmatiah (AIJER: Algazali International Journal Of Educational Research, 2020)
Abstract: Using Image Media to Improve Creative Writing Skills for Class XI Students of SMA Negeri 1 Luwu. his study aims to describe the planning, implementation, and assessment of the use of image media in improving the creative writing skills of students of class XI SMA Negeri 1 luwu. This study uses a classroom action research approach. This type of research is descriptive qualitative. This research was conducted in class XI SMA Negeri 1 Luwu in the 2018/2019 academic year. The data collection technique used in this study was the test technique and observation with two cycles. The data analysis technique used is quantitative and qualitative analysis techniques. The results showed that the use of image media in improving the creative writing skills of short story students of class XI SMA Negeri 1 Luwu was very appropriate as a learning medium. This can be seen in the implementation of planning, implementation, and assessment in cycles I and II which shows that the use of image media in improving short story creative writing skills in class XI students of SMA Negeri 1 Luwu shows significant results which are marked by an increase in the number of students who has a very high and high score category as well as a decrease in the category level of middle and low students. Use of image media in order to improve learning skills.